Guardians of Torfjanka Park. The fight for “our Moscow” and the understanding of “ordinary people” in the current conjuncture. - Reznikova, Olga (Routledge, 2021)
People in a residential district in Moscow (Torfjanka) have opposed the construction of a church in a park through direct action for more than four years. Based on material obtained during ethnographic research at that time, this chapter argues that a new type of city-oriented subjectification for Moscow residents emerges in such “local protests,” and it discusses its political implications. Awaking from “passiveness” and viewing oneself as an “ordinary person,” protecting one’s local interest is part of an understanding of being a good urban citizen who takes care of a proper city and keeps away from politics. Despite their antipolitical rhetoric, these residents define parks in Moscow in new ways as public places. They insist on their secularity and on preventing further privatization. At the same time, references to local citizens’ birthrights and root metaphors have strong exclusionary aspects that this chapter also discusses.
Keywords: Stadtsoziologie; Stadtbewohner; Sozialer Konflikt; Wertvorstellung; Stadtpark; Öffentlicher Raum; Ausgrenzung; Besetzung; Alternativbewegung